Bis(6‐methylene‐2, 2′‐bipyridine)phenylphosphine—A Flexible Ligand for the Construction of Trinuclear Coinage‐Metal Complexes. Issue 50 (1st June 2017) - Schäfer, Sebastian; Gamer, Michael T.; Lebedkin, Sergei; Weigend, Florian; Kappes, Manfred M.; Roesky, Peter W.
Abstract: Bis‐(6‐methylene‐2, 2′‐bipyridine)phenylphosphine (PN4 ) was designed as a tailor‐made ligand with different metal binding sites (N and P) to support metallophilic interactions between the different coinage metals, as these are far less common than homometallic interactions, typically between gold(I) ions. Furthermore, the phosphorus(V)sulfide derivative ofPN4 was synthesized to get additional structural information in the solid state. Two mononuclear gold complexes [(PN4 )AuCl] and [(PN4 )2 Au]ClO4 were synthesized first. Then, the two hetero trimetallic gold complexes [(PN4 )2 AuAg2 ](OTf)3 (Tf=triflate) and [(PN4 )2 AuCu2 ](OTf)3 were synthesized by selectively filling the bipyridine coordination compartments with the lighter coinage metals. For comparison two trinuclear silver complexes, that is, [(PN4 )2 Ag3 ]OTf and [(PN4 )(py)2 Ag3 (μ‐Cl)(μ3 ‐Cl)]ClO4 (py=pyridine) were prepared. All compounds were fully characterized including single‐crystal X‐ray diffraction, 15 N, 19 F and 109 Ag NMR spectroscopy. The photophysical properties of the new compounds were determined in the solid state. These revealed a different behavior between the Au–Cu and Au–Ag/Ag–Ag compounds. [(PN4 )2 AuAg2 ](OTf)3 was found to be the brightest emitter. Time‐dependent density functional calculations were performed to illuminate the differences in the photophysical properties. Abstract : Coinage‐loving ligand : The ligand bis(6‐methylene‐2, 2′‐bipyridine)phenylphosphine was synthesized to provide metallophilic interactions between different coinage metals by presenting different metal binding sites. A series of complexes was prepared (see figure) and investigated with regard to structural and photophysical properties.